DEMONSTRTIVE PLACARDS TO TEACH STORY TELLING OF SMA NEGERI 1 SUNGAI AMBAWANG - Hidayati, Septia Putri; Sutapa Y, Y. Gatot; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this study was to find out whether or not it is effective to use Demonstrative Placards to Teach Story Telling to the Tenth Grade students of SMA Negeri 1 Sungai Ambawang. The form of this research was quasi experimental. The population of this research was all of the Tenth Grade students of SMA Negeri 1 Sungai Ambawang in academic 2016/2017. There are six classes in that school. The sample of this research was chosen by using cluster random sampling in which class X IPA3 as the experimental group and the class X IPS2 as the control group, each class which consisted of 38 students. The data was collected by using measurement technique and the tool of data collection was oral performance. Using measurement technique the data used to see the null hypothesis to was higher than tt. Referring to the research finding, the researcher recommends the teacher at that school to use this technique as variation in teaching process, especially in teaching speaking narrative text. Keywords: Demonstrative Placards, Storytelling, Quasi-experimental research